Knowledge Management in the Digital Age: Harnessing Information and Innovation with Knowledge Management Systems - Nurnaninsih A; Ahmad Muktamar B; Hanifah Nurul Muthmainah (Eastasouth Institute, 2023)
In the dynamic landscape of the digital age, effective knowledge management has become paramount for organizations aiming to harness information and drive innovation. This research paper delves into the intricate interplay between knowledge management, information leveraging, and innovation within the context of the digital era. Leveraging the power of bibliometric analysis, this study examines the trends, influential authors, key concepts, and research gaps in the field. Knowledge Management Systems (KMS) emerge as crucial tools, facilitating the storage, sharing, and creation of knowledge. By systematically analyzing scholarly literature, this research contributes to a comprehensive understanding of knowledge management's evolving role in the digital age, shedding light on its implications for both theory and practice.